Assessing The Efficiency Of Urban Co-Operative Banks In India - Swati Raju (The Central European Review of Economics and Management (CEREM), 2018)
Aim: Urban Co-operative Banks are a small segment albeit significant constituent in the multi-stage credit delivery mechanism of the banking sector in India. These banks have an organisational, managerial and regulatory structure different from commercial banks. It is, therefore, of interest to study the efficiency with which these banks perform their core banking and off balance sheet activities. This paper focuses on the measurement of efficiency in the conduct of core banking and off balance sheet activities for the period 2013-14 to 2015-16.~Design / Research methods: The main idea is to employ the parametric Stochastic Frontier Analysis and the non-parametric Data Envelopment Analysis to measure the efficiency of Urban Co-operative Banks. We estimate two models for both the frontier methods, Model A examines the efficiency in core banking activity and Model B for the off balance sheet activities. The analysis of super efficiency undertaken helps identify the most efficient bank while the quartile analysis provides an insight into the distribution of efficiency (for both Models A and B). A Tobit model (for both Models A and B) has also been estimated to identify the determinants of efficiency.~Conclusions / findings: We find that Urban Co-operative banks display a higher mean efficiency in core banking activities (Model A) as compared to the off-balance sheet activities (Model B) and this finding has been reiterated by the frequency distribution of efficiency for both the frontier methods. The difference is the mean efficiency obtained for Models A and B is much wider under the stochastic frontier analysis. The analysis of super efficiency points out that of the three banks efficient under Model A and five efficient banks under Model only one bank is common to both the models. The quartile analysis highlights that 38.9 percent of the UCBs are ranked in the lower two quartiles of efficiency. The Tobit regression model has identified deposits and loans disbursed as significant determinants of efficiency for both models.~Originality / value of the article: This study contributes significantly to the existent gap in the literature on efficiency measurement of banks in India by focussing on efficiency measurement among urban co-operative banks who play an important role in urban financial inclusion.~Implications of the research: This study is the only study that has measured the efficiency in operations of Urban Co-operative Banks and can hence provide an insight into the operations of these banks. It can also help individual banks in taking appropriate measures to improve efficiency.
Keywords: E5; C6; 330; Urban Co-operative Banks; Efficiency